Análisis espectroscópico de sedimentos de estuario tropical en el nordeste de Brasil - De Paula Filho, Francisco José (2019)
The purpose of this work is to characterize the geochemical composition of sediments of the Parnaíba River delta, in terms of trace metal concentrations, using spectroscopic techniques. A profile sampling campaign was carried out in April 2017. The granulometric analysis of the surface sediments showed that the silt + clay fraction added up to 14.31% of the total. The mean concentrations of heavy metals in the profiles were 1.78 mg.kg-1 for Cd; 10.57 mg.kg-1 for Cr; 11.85 mg.kg-1 for Cu; 24.42 mg.kg-1 for Ni; 47.90 mg.kg-1 for Zn; 152.45 mg.kg-1 for Pb; 1887.28 mg.kg-1 for Mn; 1.12% for Al and 3.49% for Fe. Scanning electron microscopy/energy dispersive spectrometry (SEM/EDS) applied to the sediments from the coast of Ceará showed the morphological diversity of sediment grains. The infrared spectra presented similar functional groups at all tested points, demonstrating that the clay minerals in the different samples probably have the same origin.